Mother’s Knowledge in Dealing with Menopause - Elsera, Chori; Sawitri, Endang; Damayanti, Anissa (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Background: Most women experience fear when approaching menopause. Menopause means the cessation of a woman's menstrual cycle, or the end of a woman's reproductive life. A woman thinks she is old when she doesn't have her period anymore. Women's ignorance about what happens before and after menopause can result in prolonged anxiety and stress. Especially in women who have an obsession with aspects of physical appearance, lack of reliance on spiritual aspects and minimal adaptive coping can lead to unexpected depression. Objective: The purpose of this study was to describe the mother's knowledge about menopause. Research Method: The research method used is descriptive quantitative with cross sectional approach. Sampling technique with total sampling (65 mothers). Data collection instrument in the form of a questonnaire to assess knowledge about menopause. Data where analyzed by univariate analysis test. Results: The result is that most of the mothers are housewives 70.8% aged around 40-50 years as much as 86.1%, most of them have high school education 56.9%. Mother's knowledge of menopause is 66.1% les.